Influencing of Weather Parameters on Pheromone Trap Catches of Cotton Bollworms - and S.D.Deshmukh2, M.Pazhanisamy1, (Recent Research in Science and Technology, 2011)
The present study revealed that the peak catches of American bollworm were observed during 37th (34.77 moth trap/week), 43rd (11.25 /trap/week) and 48th meteorological weeks (MW) (11.75/trap/week). The peak activity of spotted bollworm was observed from 39th to 45 MW where the population was in the range of 8.15 to 11.15 moth/ trap/week. Six peak catches of pink bollworm were observed during 45th MW (156.9/trap/week), 46th MW (186.1 trap/week), 47th MW (390/trap/week), 48th MW (432.5/trap/week), 49th MW (306.2/trap /week) and 50th MW (148.5/trap/week). The rainfall had no significant correlation with trap catches of all three bollworms, while the trap catches of Helicoverpa armigera were positively and significantly correlated with minimum temperature, evening relative humidity and wind speed of either current week or previous weeks. Whereas sunshine hours of current and previous weeks had a negative relation with trap catches of H. armigera. The current and previous week of maximum and minimum temperature were found to be positive and significant correlation with trap catches of Earias vitella while Pectinophora gossypiella had negative correlation with either current and previous weeks of morning and evening relative humidity.